Mainstems: A logical data model implementing mainstem and drainage basin feature types based on WaterML2 Part 3: HY Features concepts. (January 2021) - Blodgett, David; Johnson, J. Michael; Sondheim, Mark; Wieczorek, Michael; Frazier, Nels
Abstract: The Mainstems data model implements the catchment and flowpath concepts from WaterML2 Part 3: Surface Hydrology Features (HY_Features) for persistent, cross-scale, identification of hydrologic features. The data model itself provides a focused and lightweight method to describe hydrologic networks with minimum but sufficient information. The design is intended to provide a model for data integration that can be used for network navigation and persistent hydrologic indexing (hydrographic addressing) functionality. Mainstems is designed to provide long-term stability with minimal maintenance requirements. The data model is not meant to advance hydrologic process representation or uniquely represent geomorphic characteristics. The principle assumption in Mainstems is that all drainage basins have one - and only one - headwater source area and a single mainstem that flows to a single outlet . Using these base feature types, ( headwater, outlet, mainstem, and drainage basin ) a nested set of drainage basins - and the associated dendritic network of mainstems - can be identified. Graphical abstract: UML class diagram showing classes and associations from HY_Features and those introduced. As subclasses, drainage basin and mainstem inherit the associations of catchment and flowpath. More specific associations, contributingDrainageBasin and primaryFlowpath are introduced. Image 1 Highlights: Introduces a data model for hydrologic indexing and data integration. Shows that a lightweight data model can integrate diverse and complex datasets. Provides a simple dendritic data model that allows representation of divergences. Provides a stable backbone for future data and tools.